2021
DOI: 10.1007/s11356-021-15334-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics and budgeting in a semi-enclosed coastal hypersaline lagoon

Abstract: Biogeochemical and ecological responses to limited external nutrient loading are poorly understood in tropical semi-enclosed coastal lagoons which are highly influenced by hydrological and salinity regimes. With objectives towards ecosystem sustainability via better management of the nutrient inputs, investigations were carried out to estimate the water, salt, and nutrient budget of "Pulicat" hypersaline coastal lagoon for the year 2018-2019. The budget revealed that the annual rate of precipitation and evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In choked‐type lagoons such as Coorong, internal loading to the water resulting from the benthic regeneration of nutrients within the sediment plays an important role in nutrient budgets and can contribute a similar amount as external loadings (Kjerfve, 1994; Vijay et al., 2021). It was therefore a focus of the CDM setup to faithfully resolve variation in the internal nutrient loads from the sediment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In choked‐type lagoons such as Coorong, internal loading to the water resulting from the benthic regeneration of nutrients within the sediment plays an important role in nutrient budgets and can contribute a similar amount as external loadings (Kjerfve, 1994; Vijay et al., 2021). It was therefore a focus of the CDM setup to faithfully resolve variation in the internal nutrient loads from the sediment.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical methods have been developed for conservative and non‐conservative mass balance assessments of coastal lagoons (e.g., Vijay et al., 2021; Vybernaite‐Lubiene et al., 2022), for the purposes of assisting in quantifying the rates of nutrient retention or export, relative to incoming nutrient loads. However, these methods are most applicable to systems with simple morphometry and environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the ecosystem study, different physical, chemical, and biological parameters were collected at regular monthly intervals from September 2018 to August 2019 along the entire Pulicat. The salinity in the lagoon varied from euhaline to hypersaline (Aug-2018 to Aug-2019) due to decreased freshwater ux, narrowing and closing of lagoon inlets, and evaporation (Vijay et al 2021). Given the regime shifts in salinity due to the decrease in WSA, it is necessary to collectively understand the WSA dynamics and their implications on the ecosystem.…”
Section: Pulicat Lagoonmentioning
confidence: 99%
“…This can result in increased levels of pollution and eutrophication, which can have negative impacts on aquatic life and human health. The budgeting of the Pulicat lagoon revealed that the decrease in precipitation and increased evaporation caused nutrient enrichment transforming the lagoon from a mesotrophic to a eutrophic system (Vijay et al 2021). The decrease in water spread area can also lead to a reduction in carbon sequestration capacity, as there is less area for the storage of organic matter while releasing the carbon trapped in the soil (Skwierawski 2022).…”
Section: )mentioning
confidence: 99%